Elderly versus younger patients with hereditary angioedema type I/II: patient characteristics and safety analysis from the Icatibant Outcome Survey. Issue 1 (19th July 2019) - Bygum, Anette; Caballero, Teresa; Grumach, Anete S.; Longhurst, Hilary J.; Bouillet, Laurence; Aberer, Werner; Zanichelli, Andrea; Botha, Jaco; Andresen, Irmgard; Maurer, Marcus; ,; Aberer, W.; et al.
Abstract: Background: Hereditary angioedema with C1 inhibitor deficiency (C1‐INH‐HAE) is characterized by recurrent swelling in subcutaneous or submucosal tissues. Symptoms often begin by age 5–11 years and worsen during puberty, but attacks can occur at any age and recur throughout life. Disease course in elderly patients is rarely reported. Methods: The Icatibant Outcome Survey (IOS) is an observational study evaluating the safety, tolerability, and efficacy of icatibant. We conducted descriptive analyses in younger (age < 65 years) versus elderly patients (age ≥ 65 years). Here, we report patient characteristics and safety‐related findings. Results: As of February 2018, 872 patients with C1‐INH‐HAE type I/II were enrolled, of whom 100 (11.5%) were ≥ 65 years old. Significant differences between elderly versus younger patients, respectively, were noted for median age at symptom onset (17.0 vs 12.0 years), age at diagnosis (41.0 vs 19.4 years), and delay between symptom onset and diagnosis (23.9 vs 4.8 years) (P ≤ 0.0001 for all). Median age at diagnosis was significantly higher in elderly patients regardless of family history (P < 0.0001). Throughout the study, icatibant was used to treat 6798 attacks in 574 patients, with 63 elderly patients reporting 715 (10.5%) of the icatibant‐treated attacks. No serious adverse events (SAEs) in elderly patients were judged to be possibly related to icatibant, whereas two younger patients reported three possibly related SAEs. Excluding off‐label use and pregnancy (evaluated for regulatory purposes), the percentage of patients with at least one possibly/probably related AE was similar for elderly (2.0%) versus younger patients (2.7%). No deaths linked to icatibant treatment were identified. All related events in elderly patients were attributed to general disorders/administration site conditions, whereas related events in younger patients occurred across various system organ class designations. Conclusions: Elderly patients with C1‐INH‐HAE were significantly older at diagnosis and had greater delay in diagnosis than younger patients. Elderly patients contributed to approximately 10% of the icatibant‐treated attacks. Our analysis found similar AE rates (overall and possibly/probably related) in icatibant‐treated elderly versus younger patients, despite the fact that elderly patients had significantly more comorbidities and were receiving a greater number of concomitant medications. Our analysis did not identify any new or unexpected safety concerns.